MANAJEMEN KONFLIK DI PERGURUAN TINGGI ISLAM STUDI KASUS KONFLIK PEMILIHAN REKTOR DI UIN MALIKI MALANG, IAIN SULTAN THAHA SYAIFUDDIN JAMBI, IAIN MATARAM, DAN IAIN IMAM BONJOL - Fridiyanto Fridiyanto (Universitas Islam Negeri Sumatera Utara Medan, 2018)
The Rector election in Islamic Higher education has made conflicts that disturb their performances. Caused of conflict are dualism leadership and resistance acts in university life. It is important for Islamic higher education to minimalize conflict in political event of rector election. Ministry of Religious Affair is recommended to make a new system in rector election to ensure Islamic higher education in good governance. Keywords: conflict, leadership, political event